The chronic need to improve the management of pain - Eldon Tunks (Pain Research and Management)
In this issue, Drs Morley-Forster, Clark, Speechley and Moulin report on their survey conducted by Ipsos-Reid in June 2001 (pages 189-194). Only physicians who met the eligibility criteria of having written 20 or more prescriptions for moderate to severe pain in the preceding four weeks or having devoted 20% of their time to palliative care were eligible to participate. Sixty-eight per cent of the respondents thought that moderate to severe chronic pain was not well managed in Canada. Despite this opinion, 23% of physicians in palliative care practice and 34% of primary care doctors stated that they would not use opioids to treat moderate to severe chronic noncancer pain even as a third-line treatment after two previous medications had failed. One-quarter to one-third were concerned about the potential for addiction, and a smaller percentage reported concern about the potential for patient abuse and/or misuse, and side effects. Fear of a College audit resulting in the loss of their medical licence was cited by 10% of primary care physicians. When asked what obstacle hindered their use of strong opioid analgesics, an unexplained 10% of palliative care doctors and 14% of primary care doctors answered "nothing in particular".